Karakteristik kimia dan organoleptik set yoghurt buah campolay (Pouteria Campechiana) dengan variasi lama inkubasi - Karina Wijaya (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2026)
Campolay fruit yoghurt set is a fermented milk drink that is beneficial for the body because it contains various nutrients. This research aims to determine the effect of variations in incubation time on the chemical and organoleptic characteristics of Campolay fruit yoghurt sets and to determine the best incubation time for yoghurt sets that meet SNI. This research used a Completely Randomized Design (CRD) with 4 treatment levels and 3 repetitions, namely P1 (incubation time for 5 hours), P2 (incubation time for 6 hours), P3 (incubation time for 7 hours), P4 (incubation time for 8 hours). The results showed that variations in incubation time had a significant effect on the water, fat, vitamin C, protein and lactic acid content but had no significant effect on the ash content and organoleptic values of the attributes of taste, aroma, color, appearance and the overall set of Campolay fruit yoghurt. The treatment for varying the incubation length of the best Campolay fruit yoghurt set is the P4 treatment (incubation time 8 hours) which produces a yoghurt set with chemical characteristics in the form of water content of 69.16%, ash content of 0.96%, fat of 2.18%, vitamin C 42, 16 mg/100gr, protein 3.21%, lactic acid 0.47% and organoleptic attributes color 2.20 (like), Aroma 2.68 (rather like), taste 2.52 (like), appearance 2.44 ( like), overall 2.46 (somewhat like).